A Drop in the Ocean: Patchy Evidence on the Societal Benefits of Marine Litter Reduction - Stoever, Jana; Rehdanz, Katrin; Okoli, Ikechukwu Charles (Frontiers in Marine Science, 2021)
The benefits of marine litter reduction to society, which are mostly non-market ones, need to be valued and quantified in monetary terms to be included in cost benefit analyses required by the EU Marine Strategy Framework Directive. This article investigates the extent to which these benefits can be derived from existing studies. We review the available empirical evidence and analyze its key characteristics based on descriptive statistics. Comparing the availability of estimates with the requirements for the EU Member States, we find a striking mismatch between the data available and the information required, which cannot be alleviated by benefit transfer. This finding is valid for both, ex-ante and ex-post, evaluation attempts. We conclude that the evidence available at present is too patchy to derive country-wide policy implications to the extent necessary to comprehensively conduct the evaluations required by the Directive.